Prevalence of skin diseases among infants in a tertiary medical facility in Uttarakhand - Bist, Jitendra Singh; Rana, Sudhir Kumar; Kumari, Neeti; Singh, Ragini; Mehta, Anil Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Skin diseases are common in infancy. This study aimed to determine to prevalence of various dermatoses in infancy in Uttarakhand. Objectives: To determine the prevalence of different dermatologic diseases in infant in Uttarakhand. Methods: A prospective study was carried out for one year from 06 Sep 2013 to 05 Sep 2014, to study prevalence and patterns of dermatological lesions in infants, a tertiary care health facility in Uttarakhand. A total of 234 infants of both sexes were seen during this period. Results: Of 234 patients 58.9% were males. Noninfectious dermatitis was the largest group of skin disorders in infancy, constituting 35.89% of total cases. Seborrheic dermatitis was commonest type of non-infectious dermatitis in infancy (42.85%) followed by atopic dermatitis (19.04%), Ptyriasis alba (14.28 %), contact and diaper dermatitis (7.14% each). Seborrheic dermatitis did not display any gender or seasonal bias. Infectious/ parasitic infestations formed second largest group of dermatoses in infants (26.92%) with commonest being fungal infections (49% cases of infectious group) followed by parasitic infestations (26.98%). Bacterial and viral infections were formed only 12.69% and 11.11% of infectious group cases. Nonfungal and nonparasitic infections showed higher incidence in summers. Conclusion: Out of 234 infants who attended paediatric dermatology clinic, major dermatoses were of noninfectious origin with seborrheic dermatitis forming largest group. Infectious etiology dermatoses constituted second major group with fungal and parasitic etiology. Nonfungal and non-parasitic dermatoses showed higher prevalence in summer months.